Dual-Reporting Transcriptionally Linked Genetically Encoded Fluorescent Indicators Resolve the Spatiotemporal Coordination of Cytosolic Abscisic Acid and Second Messenger Dynamics in Arabidopsis. Issue 8 (29th May 2020) - Waadt, Rainer; Köster, Philipp; Andrés, Zaida; Waadt, Christian; Bradamante, Gabriele; Lampou, Konstantinos; Kudla, Jörg; Schumacher, Karin
Abstract : Multiparametric in vivo analyses using dual-reporting genetically encoded fluorescent indicators reveal the spatiotemporal coordination of signaling compound dynamics in Arabidopsis roots. Abstract: Deciphering signal transduction processes is crucial for understanding how plants sense and respond to environmental changes. Various chemical compounds function as central messengers within deeply intertwined signaling networks. How such compounds act in concert remains to be elucidated. We have developed dual-reporting transcriptionally linked genetically encoded fluorescent indicators (2-in-1-GEFIs) for multiparametric in vivo analyses of the phytohormone abscisic acid (ABA), Ca 2+, protons (H + ), chloride (anions), the glutathione redox potential, and H2 O2 . Simultaneous analyses of two signaling compounds in Arabidopsis ( Arabidopsis thaliana ) roots revealed that ABA treatment and uptake did not trigger rapid cytosolic Ca 2+ or H + dynamics. Glutamate, ATP, Arabidopsis PLANT ELICITOR PEPTIDE, and glutathione disulfide (GSSG) treatments induced rapid spatiotemporally overlapping cytosolic Ca 2+, H +, and anion dynamics, but except for GSSG, only weakly affected the cytosolic redox state. Overall, 2-in-1-GEFIs enable complementary, high-resolution in vivo analyses of signaling compound dynamics and facilitate an advanced understanding of the spatiotemporal coordination of signal transduction processes in Arabidopsis.